The first observation of an optical counterpart to a short gamma‐ray burst from the Czech Republic: GRB 160927A. Issue 7 (30th October 2019) - Trčka, Šimon; Jelínek, Martin; Štrobl, Jan
Abstract: We present the earliest observations of the short Gamma‐Ray Burst, GRB 160927A, by the D50 telescope from the Ondřejov Observatory. The 50‐cm robotic telescope reacted to the alert of GRB 160927A and started obtaining unfiltered images 40 s after the trigger with a total exposure of 7, 230 s. The magnitude obtained by D50 reached 22.4 ± 0.3 mag not corrected for the galactic foreground extinction of 0.2 mag. We obtained the temporal decay index with α  = 0.93 ± 0.03 and the spectral slope with β  = 0.68 ± 0.2.